Respuesta :

Step-by-step explanation:

An equation to keep in mind is y=mx+b

m= [tex]\frac{y_{2}-y_{1} }{x_{2}- x_{1} }[/tex]

Any two coordinates would be good for this formula

For example you could use (2, -4) and (3, -7)

(3, -7) would be your second coordinate

(2, -4) would be your first coordinate

-7 = [tex]y_{2}[/tex]

3= [tex]x_{2}[/tex]

-4= [tex]y_{1}[/tex]

2= [tex]x_{1}[/tex]

Put the values into the formula and solve

[tex]\frac{-7-(-4)}{3-2}[/tex]= [tex]\frac{-7+4}{1}[/tex] = [tex]\frac{-3}{1}[/tex]= -3

m= -3

Now you have y=-3x +b

There are 2 ways to find b, but I will show the one that is the easiest to explain for me

1) substitute the x and y coordinates from one of the coordinates into the 'new' formula

I will be using the coordinate (2,-4)

y = -3x + b

-4 = - 3(2) +b

-4 = -6 +b

-4 +6 = -6 +6+b

2 = b

Your updated equation is y=-3x+2

The answer is the second option

I hope this helps!!!